A novel particle swarm optimisation self-regulating stand-alone wave energy conversion scheme. (1st November 2010) - Sharaf, Adel M.; El-Gammal, Adel A.A.
The paper presents a novel stabilisation scheme system for a wave energy converter (WEC) using permanent magnet linear generator (PMLG) connected to a six-pulse diode rectifier. The proposed controller of WEC-battery renewable energy system is based on multi-objective particle swarm optimisation (MOPSO) technique. The optimisation algorithm is implemented to control a novel low cost dynamic AC side filter/capacitor compensation scheme. The novel dynamic modulated filter capacitor compensation (MPFC) scheme serves as an AC side voltage stabilisation regulator and wave energy utilisation enhancement. The objective is to extract available power from the wave energy system (WES) and transfer this power efficiency to the local isolated DC side electric load. The performance and dynamic characteristics of the controllers to any load non-linear J, B parameters and load torque excursions is examined for PMDC motor drives. A tri-loop error-driven dynamic controller is used to adjust the PWM switching of the two dynamic filter compensator schemes. A multi-objective optimisation MOPSO technique is used to find the dynamic optimal control settings of the control signal to the PWM activation/triggering block that dynamically minimises the global dynamic error for all components, three SPWM, switched filters and motor.